2022
DOI: 10.1002/aur.2710
|View full text |Cite
|
Sign up to set email alerts
|

Subject‐performed task effect on working memory performance in children with autism spectrum disorder

Abstract: A previous study found that children with autism spectrum disorder (ASD) have better recall when they perform instructions (subject‐performed task [SPT]) than when they passively hear instructions (verbal task [VT]) in a working memory task for instructions, an effect that is called the SPT effect. This study explored whether the SPT effect exhibited by ASD children is caused by the movement component or by processing materials twice. More importantly, this study explored whether intelligence influences the SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…However, the comparison between them was regulated by the encoding direction, and significant differences were observed in either direction (the same or opposite direction relative to the observed direction). Learning movements by imitation involves the same or opposite direction relative to the observed direction, while performing movements without imitation does not involve direction (e.g., performing a movement consistent with an action phrase, such as knocking on the door in a verbal working memory task; see Allen et al, 2019; L. J. Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the comparison between them was regulated by the encoding direction, and significant differences were observed in either direction (the same or opposite direction relative to the observed direction). Learning movements by imitation involves the same or opposite direction relative to the observed direction, while performing movements without imitation does not involve direction (e.g., performing a movement consistent with an action phrase, such as knocking on the door in a verbal working memory task; see Allen et al, 2019; L. J. Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our finding that arm and leg movements do not differ in working memory performance when the encoding direction is not considered has important enlightening significance for studies of embodied cognition that also focus on limb movements but do not involve motor learning (without imitation). Studies have generally found that individuals can recall verbal instructions better when they physically perform instructions than when they only hear instructions, a phenomenon called the “enactment effect” (Allen et al, 2019; L. J. Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported beneficial effects of EE on long‐term memory in individuals with ASD with average and high cognitive abilities (Grainger et al, 2014; Yamamoto & Masumoto, 2018; Zalla et al, 2010). Moreover, beneficial effects of EE on working memory were found in autistic children with lower middle and higher levels of intelligence (Wang et al, 2022), though some evidence suggests that EE might be less effective in ASD than in typically developing children (Xie et al, 2024). While there are no studies that have specifically examined EE as an encoding strategy for PM performance in autistic individuals, its beneficial effects have been shown in other populations with difficulties in executive functions and episodic memory (Pereira et al, 2015, 2018).…”
Section: Introductionmentioning
confidence: 99%